2014
DOI: 10.4103/0300-1652.137197
|View full text |Cite
|
Sign up to set email alerts
|

Early outcome of incisional hernia repair using polypropylene mesh: A preliminary report

Abstract: Background:The use of prosthetics for open repair of incisional hernia is very recent in our practice. We highlight our experience repairing incisional hernias with polypropylene mesh.Patients and Methods:Patients presenting with incisional hernia >5 cm in length or width received open polypropylene mesh repair and were followed for two years. Data obtained included age, sex, primary surgery causing the hernia, the length of the fascial defect and previous attempts at repair. Post-operative wound complications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Seroma collection is an inflammatory response[ 16 17 ] which intensity depends on the mesh-tissue area of contact; it is minimal with inguinal hernioplasty because the implanted mesh dimension is small and tissue dissection is minimal. Much of the seroma gets absorbed and does not require intraoperative placement of a drain but in the event of its occurrence postoperatively can be adequately treated by aseptic aspiration.…”
Section: Discussionmentioning
confidence: 99%
“…Seroma collection is an inflammatory response[ 16 17 ] which intensity depends on the mesh-tissue area of contact; it is minimal with inguinal hernioplasty because the implanted mesh dimension is small and tissue dissection is minimal. Much of the seroma gets absorbed and does not require intraoperative placement of a drain but in the event of its occurrence postoperatively can be adequately treated by aseptic aspiration.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,6 Incisional hernias can present almost soon after the primary surgery or several years after. 4,5,10 The two cases reported here did not seek medical advice many years after the primary surgery, even though the swellings were noticed about a year after the primary surgery. Several authorities have reported that patients with incisional hernias only seek surgical repair because of physical discomfort or complications.…”
Section: Discussionmentioning
confidence: 85%
“…They opined that a balance between costly cutting-edge and affordable surgical practice as well as adequate training of general practitioners and surgical trainees, will result in a low postoperative complication profile and reduce the incidence of incisional hernias, which often present with complications. Udo et al 10 in a prospective report of the early outcome of incisional hernia repairs in Uyo, southern Nigeria, noted that only a few patients with incisional hernias seek medical advice. This trend, they attributed to the high cost of treatment and disappointment from previous failed surgeries and repairs.…”
Section: Discussionmentioning
confidence: 99%
“…Indian J Case Reports 496 section [4][5][6][7]. Our patient had a history of laparotomy and total abdominal hysterectomy.…”
Section: Vol 4 | Issue 6 | Nov -Dec 2018mentioning
confidence: 99%